Do hobbies matter in resume screening? – Evidence from an eye-tracking study - Pyhäranta, Iida (fi=Turun yliopisto|en=University of Turku|, 2018)
A practice of hiring for cultural fit has grown popular in the business sphere. Recruiters want to find job candidates that best fit the company’s culture, emphasizing benefits for job satisfaction and commitment. However, little is known about how the seek for cultural fit influences hiring decisions. One alarming notion is that cultural fit may override concerns about actual job performance. This is a particularly potent risk in the fast resume screening phase of hiring. In this thesis, I explore how recruiters’ perspective influences the attention paid to resume sections. I hypothesize that when reading resumes from a cultural fit perspective, recruiters pay more attention to information that is unrelated to candidates’ competence for the job (such as hobbies). I also examine how job candidates’ hobbies listed on their resumes influence fit perceptions and hiring decisions. I investigate this with an experiment where participants’ eye movements were tracked while they read and rated resumes. The experiment was conducted at an international, elite business school in France. 60 MBA students participated in the experiment, in which their task was to hire a consultant to their imaginary team in a management consulting company. Prior to the actual task, participants’ perspective was modified with a priming procedure where they read a text emphasizing the importance of hiring for either cultural fit or analytical skills. During the resume reading task, participants’ eye movements were tracked. After reading, participants rated each resume on three measures. Half of the resumes were culturally fit and half of them were unfit. Cultural fitness was manipulated with hobbies marked on the resumes that either matched or mismatched the jobholder schema of a consultant. A pre-study was conducted to retrieve such hobbies. The resulting eye movement and resume rating data was statistically analyzed with ANOVA procedures. The results show that recruiters’ perspective influences the way they screen resumes. Recruiters seeking for cultural fit pay more attention to unfit hobbies and work experience. The results also show that hobbies matter in hiring. Candidates with consultant stereotype congruent hobbies receive better evaluations and more likely proceed in the hiring process. Hobbies affect fit perceptions regardless of the recruiters’ perspective. The results suggest that recruiting companies should inspect their resume screening processes to avoid biased hiring decisions. They should also break down the jobholder schemas used in their organization to ensure that decisions are not based on invalid criteria such as candidate hobbies. More academic research is needed to reveal the decision-making process in resume screening. Particularly, work experience’s relation to cultural fit perceptions calls for further studies.